The combined effect of plastic orthotropy and tension-compression asymmetry on the development of necking instabilities in flat tensile specimens subjected to dynamic loading. (1st March 2019) - N'souglo, K.E.; Rodríguez-Martínez, J.A.; Vaz-Romero, A.; Cazacu, O.
Highlights: High-purity α -titanium flat tensile specimens subjected to dynamic loading. Effect of plastic orthotropy and tension-compression asymmmetry on necking instabilities. Specimen orientation plays a key role in the location and characteristics of the necks. For three specimen orientations the necks contain two identical localization bands. For other orientations, the bands have different inclinations, and grow at different speeds. Abstract: In this paper we study, using finite element simulations, the combined effect of plastic orthotropy and tension-compression asymmmetry on the formation of necking instabilities in high-purity α -titanium flat tensile specimens subjected to dynamic loading under a wide range of impact velocities. To this end, the material behaviour is described using the constitutive model developed by Nixon et al. (2010a), which accounts for these specific features of the plastic response of hexagonal-close-packed materials. While numerical studies have shown the effect of material properties and loading conditions on the formation and development of necking instabilities in dynamically loaded tensile specimens, none of them, to the best of our knowledge, has considered the plastic orthotropy and tension-compression asymmmetry of the material. The finite element simulations show that the orientation of the specimen with respect to the in-plane symmetry axes of the material plays a key role in the location and characteristics of the neck(s) formed in the sample. Moreover, the results indicate that only for three specimen orientations the main neck formed in the sample contains two localization bands, equally inclined with respect to the specimen axis, which grow at equal speed. For all other orientations, the localization bands have different inclinations, and one grows faster than the other one.